Jentayu Bridal Boutique / Arfah Mohd. Idris ... [et al.] - Mohd. Idris, Arfah; Chek Dollah, Marina; Noh, Fauzilatuanisa; Robert Bidi, Kevin Jantan; Musa, Khairin Syaziyah (Faculty of Hotel and Tourism Management, 2004)
The name of our business is Jentayu Bridal Boutique. The natures of our business are to provide product and services of bridal wear and accessories. We also provide packages for bridal wear, make up and accessories. Our business date of commencement will be on 15th March 2004. Factors in selecting the proposed business: • Interest in business prospect • Interest in the industry itself • Knowledge and skill in that particular area of expertise Industry profile: Bridal wear industry has long existed ever since there were marriages. It is known that couples that were heading for the isle (marriage) would need services and products to make it a memorable day. Not only do they need products that are of quality but it also has to be in trend according to the era. Usually to be a bride and groom needs to be prepared financially to enable them to make the appropriate preparation for the wedding day. They would also set aside a sufficient si}n of money just for the bridal dress and for the reception. It is important for the bride and groom to look their best on that day as it should be a once in a lifetime experience. That is the reason for us opening a bridal business. We would like to be the one to provide happy couples with the most suitable products and services during the special event and to make it an even more memorable moment.